Impact of telenursing on blood pressure and body mass index of people with prehypertension: A randomized controlled clinical trial - Habib Sadeghi-Gandomani; Zahra Habibi; Maryam Eghbali-Babadi; Alireza Khosravi (Wolters Kluwer Medknow Publications, 2021)
Background: Prehypertension is an important global health challenge. This study determines the effect of telenursing on Blood Pressure (BP) and Body Mass Index (BMI) in patients with prehypertension. Materials and Methods: This randomized controlled clinical trial study included 81 patients with prehypertension discharged from an emergency room at Isfahan University of Medical Sciences (Iran) in 2016. Participants joined a session about hypertension, risk factors, and lifestyle modification to reduce its risk. Using a random number table, 41 subjects were assigned to the experimental group and 40 subjects to the control group. Only the experimental group received four SMS messages each week and a 10-15 min phone call once a month to help them change their lifestyle and reinforce their health behaviors. Eventually, patients' information was collected, and the data were analyzed using independent t, paired t, and Chi-square tests. Results: The experimental group after the intervention had a significantly lower mean (Standard Deviation [SD]) of Systolic Blood Pressure (SBP) (from 126.67 [5.15] to 119.21 [5.72] [t40 = 8.40, p < 0.001]) and Diastolic Blood Pressure (DBP) [from 85.28 (2.29) to 78.79 (4.16) (t40 = 10.02, p < 0.001)]. However, the same means were not significantly different in the control group [SBP (p = 0.116) and DBP (p = 0.096)]. The mean (SD) of changes between BMI before and after the intervention was -0.75 (0.66) in the experimental and 0.042 (0.41) in the control group, which was significantly different between the two groups (t79= -6.44, p < 0.001). Conclusions: Telenursing can have potential benefits to maintain BP within the normal range and reduce BMI in patients with prehypertension.